Years and Years. Temps et politisation - Antoine Faure; Emmanuel Taïeb (ReS Futurae)
In turns dystopia and utopia, Years and Years is a social science fiction show which examines the links between time and politicization. Its projection into the future is accelerated by the rapid passage of history broadcast by media summaries of the main events that upset the social, political, economic and technological processes of the diegetic world. Along the way, the characters become politicized in the sense that they enter or experience politics. This text examines how, in the diegesis, the process of politicisation is discussed through seriality and the accelerated staging of social temporalities, and how these temporal arrangements make political proposals for anticipating the near future, including the various uses of digital technologies.